2021
DOI: 10.1097/olq.0000000000001540
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anatomic Site, Specimen Collection Timing, and Patient Symptom Status on Neisseria gonorrhoeae Culture Recovery

Abstract: Background: Neisseria gonorrhoeae culture is required for antimicrobial susceptibility testing, but recovering isolates from clinical specimens is challenging. Although many variables influence culture recovery, studies evaluating the impact of culture specimen collection timing and patient symptom status are limited. This study analyzed urogenital and extragenital culture recovery data from Centers for Disease Control and Prevention's Strengthening the US Response to Resistant Gonorrhea (SURRG) program, a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 29 publications
3
27
0
Order By: Relevance
“…2020; Nash et al . 2021). In our study, as shown in Table 2, the most common site of infection was the pharynx (71·3%; 95% CI 68·0–74·6), followed by rectum (42·8%, 95% CI 39·1–46·2) and genitals (10·9%, 95% CI 8·6–13·2).…”
Section: Resultsmentioning
confidence: 99%
“…2020; Nash et al . 2021). In our study, as shown in Table 2, the most common site of infection was the pharynx (71·3%; 95% CI 68·0–74·6), followed by rectum (42·8%, 95% CI 39·1–46·2) and genitals (10·9%, 95% CI 8·6–13·2).…”
Section: Resultsmentioning
confidence: 99%
“…Culture success by anatomic site among NAATpositive patients in SURRG is reported elsewhere. 20 Of isolates that underwent AST (99.3% of positive cultures), 11% demonstrated azithromycin nonsusceptibility; fewer than 0.5% demonstrated elevated ceftriaxone or cefixime MICs (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…As expected, urethral specimens yielded positive GC cultures greater than 90% of the time and endocervical/vaginal 55%, but pharyngeal culture was even poorer than previously documented 16 : only 28% of specimens collected from a NAAT-positive individual resulted in a GC isolate. 15 Culture recovery declined in the time between NAAT collection and culture collection for all anatomic sites. These data can help refine clinical criteria for when to obtain specimens and serve as an impetus to find ways to improve isolate recovery from extragenital sites in SURRG cycle 2.…”
Section: Clinical and Laboratory Lessonsmentioning
confidence: 96%